Aberrant antibody affinity selection in SHIP‐deficient B cells. Issue 2 (12th December 2012) - Leung, Wai‐Hang; Tarasenko, Tatiana; Biesova, Zuzana; Kole, Hemanta; Walsh, Elizabeth R.; Bolland, Silvia
<x xml:space="preserve">Abstract</x> The strength of the Ag receptor signal influences development and negative selection of B cells, and it might also affect B‐cell survival and selection in the GC. Here, we have used mice with B‐cell‐specific deletion of the 5′‐inositol phosphatase SHIP as a model to study affinity selection in cells that are hyperresponsive to Ag and cytokine receptor stimulation. In the absence of SHIP, B cells have lower thresholds for Ag‐ and interferon (IFN)‐induced activation, resulting in augmented negative selection in the BM and enhanced B‐cell maturation in the periphery. Despite a tendency to spontaneously downregulate surface IgM expression, SHIP deficiency does not alter anergy induction in response to soluble hen‐egg lysozyme Ag in the MDA4 transgenic model. SHIP‐deficient B cells spontaneously produce isotype‐switched antibodies; however, they are poor responders in immunization and infection models. While SHIP‐deficient B cells form GCs and undergo mutation, they are not properly selected for high‐affinity antibodies. These results illustrate the importance of negative regulation of B‐cell responses, as lower thresholds for B‐cell activation promote survival of low affinity and deleterious receptors to the detriment of optimal Ab affinity maturation.